Sol-gel hot injection synthesis of ZnO nanoparticles into a porous silica matrix and reaction mechanism. (5th April 2017) - Barhoum, Ahmed; Van Assche, Guy; Rahier, Hubert; Fleisch, Manuel; Bals, Sara; Delplancked, Marie-Paule; Leroux, Frederic; Bahnemann, Detlef
Abstract: Despite the enormous interest in the properties and applications of porous silica matrix, only a few attempts have been reported to deposit metal and metal oxide nanoparticles (NPs) inside the porous silica matrix. We report a simple approach (i.e. sol-gel hot injection ) for insitu synthesis of ZnO NPs inside a porous silica matrix. Control of the Zn:Si molar ratio, reaction temperature, pH value, and annealing temperature permits formation of ZnO NPs (≤ 10 nm) inside a porous silica particles, without additives or organic solvents. Results revealed that a solid state reaction inside the ZnO/SiO2 nanocomposites occurs with increasing the annealing temperature. The reaction of ZnO NPs with SiO2 matrix was insignificant up to approximately 500 °C. However, ZnO NPs react strongly with the silica matrix when the nanocomposites are annealed at temperatures above 700 °C. Extensive annealing of the ZnO/SiO2 nanocomposite at 900 °C yields 3D structures made of 500 nm rod-like, 5–7 μm tube-like and 3–5 μm needle-like Zn2 SiO4 crystals. A possible mechanism for forming ZnO NPs inside porous silica matrix and phase transformation of the ZnO/SiO2 nanocomposites into 3D architectures of Zn2 SiO4 are carefully discussed. Graphical abstract: Highlights: Sol-gel hot injection is an elegant one-pot synthesis method to disperse ZnO NPs into a porous SiO2 matrix. ZnO/SiO2 nanocomposites are thermally stable at 500 °C. Extensive annealing (˃700 °C) of ZnO/SiO2 nanocomposites forms Zn2 SiO4 structures. Zn:Si molar ratio affects significantly on morphological changes of ZnO/SiO2 nanocomposites.